Obraz duszpasterstwa polskojęzycznego w Europie na podstawie wizytacji Rektora Polskiej Misji Katolickiej w Belgii - Szymański, Józef (Archiwa, Biblioteki i Muzea Kościelne, 2012)
The Catholic church in Poland undertook steps to provide optimal pastoral care for the Polish people abroad. These activities were formalized through the creation of the Polish Catholic Missions. The first Polish Catholic Mission was created in France (1922), next one in January 1926 in Belgium. This mission extended its power over Denmark, Holland (1927). The priests who successively held the office of Rector of the Polish Catholic Missions: T. Kotowski, W. Kudłacik and R. Moskwa organized pastoral, cultural, educational life among the Polish people and left, in the form of statements and reports, the descriptions of the condition and situation of the Polish emigrants abroad.